PATHOLOGY AND STAGES OF DEVELOPMENT OF MYOCARDIAL INFARCTION (World Bulletin of Public Health, 2025)
This article provides a scientific and critical analysis of myocardial infarction, including its etiology, pathogenesis, clinical signs, and treatment methods. Myocardial infarction is a disease that can pose a significant risk to human health. The article extensively explores these aspects and analyzes them based on various medical sources. It also highlights modern diagnostic and treatment methods, as well as preventive measures. The Ministry of Health is currently developing and implementing modern strategies to prevent this and similar diseases.